The impact of implicit theories on resilience among Chinese nurses: The chain mediating effect of grit and meaning in life - Tang, Yixun; He, Changjiu; Feng, Lanling; Wu, Dongmei; Zhou, Xiaojun; Li, Tao; He, Lina; Cai, Qiao; Yue, Yuchuan (Frontiers in Psychology, 2022)
Implicit theories refer to assumptions people hold about different domains, also known as mindsets. There are two implicit theories on the malleability of one’s ability: entity theory and incremental theory. They constrain and regulate people’s understanding and responses to an individual’s behavior, leading to different social cognitive patterns and behavioral responses. Resilience is a positive adaptation in highly stressful situations that represents mechanisms for coping with and transcending difficult experiences, i.e., a person’s ability to successfully adapt to change, resist the adverse effects of stressors, avoid significant dysfunction, and be chronically affected by considered a protective factor for mental health. Although previous studies showed that individuals’ implicit theories are associated with resilience, this relationship has received little attention in the nursing population. It is unclear which variables may contribute to explaining the relationship between implicit theories and resilience. Therefore, the current study aims to deeply explore the relationship between implicit theories and the resilience of Chinese nurses. In addition, we also seek to demonstrate the chain mediating effects of grit and meaning in life on this relationship. We surveyed 709 Chinese nurses through online questionnaires using the self-made demographic questionnaire, the Implicit Theories Scale, the Short Grit Scale, the Meaning in Life Questionnaire, and the 10-item Connor-Davidson Resilience Scale. After controlling for demographic variables such as age, gender, educational background, marital status, professional title, and working years, the results reveal positive associations between Chinese nurses’ implicit theories and their resilience, and grit and meaning in life play a partial mediating role in this relationship, respectively. Furthermore, grit and meaning in life play a chain mediating role between implicit theories and resilience. These findings contribute to understanding the psychological impact mechanism of implicit theories on nurses’ resilience and provide a theoretical basis for nursing managers to formulate strategies to improve nurses’ psychological resilience.